Strategy Analysis of Non-Formal Education Service Quality at The Department of Education and Culture, Mamasa District - Darlin; Petrus; Asrin Tandi (Green Publisher, 2021)
The implementation of Non-formal Education at the Mamasa Regency Education and Culture Office is still limited in services, both in providing facilities and infrastructure, and other supports so that it is necessary to get maximum service. Research purposes to describe the quality of public and innovative services in the field of non-formal education at the Mamasa District Education and Culture Office, to realize a public service quality strategy with excellent character in the field of non-formal education at the Mamasa District Education and Culture Office. The data used in this study are primary data and secondary data. This research is a type of qualitative research. Research that describes a certain situation and object that will be studied in the current conditions, based on the facts or existing facts. Service strategies that can be carried out in the field of Non-formal Education at the Mamasa Regency Education and Culture Office with the following implementation: Implementation of advanced courses for alumni of Non-formal Education and improvement of infrastructure for supporting services for Non-formal Education, Implementing services with excellent character and creativity in service delivery, and Improvement and improvement of service quality in the field of Non-Formal Education, Mamasa Regency Education and Culture Office.